Tax Payers Moral Behavior in Nepal - Acharya, Paras Mani (Damak Campus Journal, 2023)
This study analysis the Tax Payers’ moral behavior In Nepal. Further, the Study attempts to deal in the underlying reasons for non-compliance. Data was gathered through Questioner with four hundred participants, and analyses using thematic analysis. Results suggest those taxpayers have inadequate technical knowledge and perceive VAT system as complex. Tax Knowledge and tax complexity are viewed as contributing factors towards non-compliance behavior among taxpayers. The data are collected through well structured questionnaire. For the Purpose of analysis and interpretation the researcher has used the following statistical tools of SPSS. On the basis of analysis and interpretation the researcher introduces the major findings that the majority of the consumers pay tax but, they are not much aware of the VAT. Due to the High tendency of VAT the consumers try to avoid the payment of tax in Nepal.